Implementation of Infection Prevention and Control in Health Services Reproduction in Babakansari Village, Plered District, Purwakarta - Chotimah, Husnul; Kustant, Sasya Isnaeni; Lisnawati, Rohayu (CV. Publikasi Indonesia, 2025)
Infection prevention and control (IPC) is a crucial component of reproductive health services to protect patients and healthcare workers from the risk of infection. This study aimed to evaluate the implementation of IPC in healthcare facilities in Babakansari Village, Plered District, Purwakarta. The method used was descriptive qualitative through direct observation, in-depth interviews, and document review with 20 healthcare workers and 50 patients using reproductive health services. The results showed that the implementation of IPC standards was ongoing, but there were challenges related to the availability of personal protective equipment (PPE), medical waste management, and adherence to hand hygiene procedures. In conclusion, ongoing training, routine supervision, and infrastructure improvements are needed to support optimal IPC implementation.